PENGARUH PENDEKATAN WHOLE LANGUAGE TERHADAP HASIL BELAJAR MEMBACA PEMAHAMAN BAHASA INDONESIA SISWA KELAS IV SD - Noor Alfulaila (Universitas Tadulako, 2014)
Effect of the whole language approach on the learning achievement in indonesian language reading comprehension of year IV Students of Elementary Schools. This study aims to investigate effects of whole language approach on learning achievement in indonesian language reading comprehension of groups of students based on their learning motivation. This study was an experimental study employing a 2x2 factorial design. The independent variabel had two levels, i.e. the Whole language approach and the konvensional approach. The population comprised all 46 Year IV students of SDN Madinaturramlah. The instruments consisted of an achievement test and a learning motivation questionnaire. The data were analyzed by a amean of two way ANOVA and the Scheffee test. The results show that (1) the is no difference in learning achievement between the students in the experimental group and those in the control group, (2) there is a difference in learning achievement between students with hight motivation in the experimental group and those in the control group, (3) there is no interaction between approaches and learning motivation. Keywords: Learning achievement in reading comprehension, whole language approach, learning motivation